Cryptography Converges with AI in Financial Systems: Safeguarding Blockchain Transactions with AI - Nizamuddin, Md.; Devarapu, Krishna; Onteddu, Abhishake Reddy; Kundavaram, RamMohan Reddy (Asian Business Review, 2022)
This paper examines how encryption and AI protect financial blockchain transactions. As blockchain technology grows more important in decentralized finance, AI must be included to solve cybersecurity issues. The research focuses on how AI improves cryptography systems, blockchain-based financial operations, and transaction security. Secondary data from the literature, peer-reviewed publications, and case studies are analyzed to synthesize AI-blockchain cryptography expertise. AI provides real-time anomaly identification, fraud prevention, predictive analytics, consensus mechanism optimization, and key management improvements, boosting blockchain security. Traditional cryptography methods become more adaptable and robust to emerging threats using AI. According to the research, the computational complexity of AI-driven solutions and AI model biases are constraints. Regulatory frameworks must be modified to ensure transparency, accountability, and compliance with AI-enhanced cryptography systems. This research shows that AI can strengthen blockchain transactions, indicating that AI and cryptography will shape safe and efficient financial systems in the future.